THE EFFECT OF USING CROSSWORD IN TEACHING VOCABULARY AT THE EIGHTH GRADE OF SMP HKBP SIDORAME MEDAN - Diana Lamjunida Siregar; Nurhayati Sitorus; Febrika Dwi Lestari (Sean Institute, 2023)
This study aims to know whether the use of crossword in teaching vocabulary. The researcher conducted the research at SMP HKBP Sidorame Medan. This study was carried out by Quasi-Experimental research. The object of this study was the eighth grade students at SMP HKBP Sidorame Medan. The sample of this study amounted to 20 people consisting of an experimental and a control group, with a total of 10 students for each group. To collect the data researcher used vocabulary test in pre-test and post-test. After collecting the data, the author analyzed the data. The results of this study can be seen as follows: t-count > t-table (p = 0.05) with degree of freedom (df) = 18. This means that 4.57388216>1.734 (p=0.05) with df 18. This means that the use of crossword in vocabulary teaching has a significant effect to the student at the eighth grade of SMP HKBP Sidorame Medan. Based on the results of data analysis, the experimental class students achieved better scores (from 60 to 79.5) while the control class results only showed a slight improvement (from 54.5 to 65). It can be concluded that the use of crossword puzzles is successful in teaching vocabulary to students at the eighth grade of SMP HKBP Sidorame Medan. So, teachers in schools can use this teaching method in teaching vocabulary.